Sponge-inhabiting barnacles of the Americas: a new species of Acasta (Cirripedia, Archaeobalanidae), first record from the eastern Pacific, including discussion of the evolution of cirral morphology - Van Syoc, R. J.; Winther, R. (Crustaceana, 1999)
Acasta newmani n. sp. from the Gulf of California, Mexico is described. This is the first report of Acasta from the eastern Pacific. Hypotheses are discussed concerning the correlation of cirral morphology with feeding methods and host specificity. The similarities between A. newmani and Acasta cyathus Darwin, 1854 indicate that they are examples of the common pattern of trans-isthmian sibling taxa in the Caribbean and eastern tropical Pacific. A key to the seven sponge-inhabiting barnacle species of the Americas is presented with citations noting their host sponge species and known ranges in the Americas. The range of Membranobalanus nebrias (Zullo & Beach, 1973) is extended from the Galapagos Islands to the Gulf of California.